Perlas Montessori para desarrollar las competencias matemáticas en los estudiantes de Segundo grado de la Unidad Educativa Particular San Gerardo, Loja 2024 - Tibanquiza Castro, Mildred Jazmín (2024)
Montessori pearls are manipulative tools that are used in the Montessori method. This is designed to teach children mathematical concepts in a concrete and visual way, this allows children to have independent learning and integral development. Likewise, the pearls allow the manipulation of units, tens, hundreds and thousands, developing a solid understanding of positional value and numerical structure. Likewise, this method seeks to enhance mathematical skills through manipulation and play, offering a pedagogical alternative that encourages deep understanding and autonomous learning. Therefore, this research had the purpose of analyzing the incidence of Montessori Pearls through a pedagogical proposal for the development of mathematical skills at the San Gerardo Private Educational Unit. It presented a mixed descriptive approach, as well as a quasi-experimental design, using inductive, deductive, and analytical-synthetic methods. A questionnaire of mathematical concepts was applied to 18 children through which it was determined that in the pre-evaluation 56% of the students are close to achieving the required learning, presenting difficulties in the contents on additions, subtractions, logical reasoning and placement of mathematical signs and the remaining 17% of those evaluated have achieved the required learning, showing in the application of the post- evaluation an increase of 89% mastering the required learning. Concluding that Montessori pearls are effective for the development of mathematical competencies because they strengthen in children the skills of logical reasoning, decomposition of problems, mathematical calculations and procedures, addition, subtraction, placement of mathematical signs.